A Physiological Study of Twaca w.s.r. to Effectiveness of Madhucchishta and Jatyadi Taila in Padadari (AYUSHDHARA, 2023)
Ayurveda considers Padadari under Kshudra roga which has been first described in Sushruth Samhita. Padadari is one of the most commonest and negligible diseases, highly prevalent in rural areas. Vruddha Vata Dosha is related to Padadari. It is characterised by minor to severe cracks on the feet, more frequently on the heels. In severe conditions, it causes Vedana, Daha, Rookshata and occasionally Raktasrava. Here, Madhuchchista and Jatyadi Taila being cost and medically more effective are used as remedy for Padadari. An open labelled clinical trial has been conducted to evaluate the effectiveness of Malahar prepared using Madhuchchista and Jatyadi Taila in Padadari. Material and Method: Whole pharmaceutical procedure was carried out in the sequence of Madhuchchista and Jatyadi Taila preparation. Ratio of 1:5 of Madhuchchista and Jatyadi Taila for preparing Sikta Taila was selected and prepared for the preparation of Padadari Malahar. Result: Response to the treatment was recorded on a weekly basis and therapeutic effect was evaluated through symptomatic relief. Conclusion: The study yielded statistically highly significant results in symptoms such as dryness (P